Community Perception of Moringa Leaf Noodles in Babul Makmur Village, Simeulue Barat District, Simeulue Regency - Yulia Novita; Teuku Athaillah (Britain International for Academic Research (BIAR-Publisher), 2022)
The benefits of the Moringa plant are many and almost all parts of the Moringa plant such as leaves, flowers, stems, fruit, and seeds can be used as a source of food, especially the leaves. The purpose of this study was to analyze (1) the introduction of respondents to Moringa, (2) Public Perceptions of Moringa processing and (3) Community Perceptions of Moringa Leaf Noodles. This research was conducted in Babul prosperous village, west Simeulue sub-district, Simeulue district. The time of the research was carried out in November 2021. The research was conducted by interviewing 50 respondents. Data collection used Likert Scale analysis. From the results of the study, it was found that the average score for the introduction of the community to the Moringa plant was 3.96. Where the score shows that the community agrees that they are familiar with the Moringa plant. The value of the average score of public perception of Moringa processing is 3.76. Where the score shows that people agree that Moringa can be processed into a variety of dishes. The value of the average score of public perception of Moringa leaf noodles is 4.05. Where the score shows that people agree that Moringa leaf noodles are delicious and the ingredients are easy to find.